2021
DOI: 10.1038/s41467-021-26828-1
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian SWI/SNF chromatin remodeler is essential for reductional meiosis in males

Abstract: The mammalian SWI/SNF nucleosome remodeler is essential for spermatogenesis. Here, we identify a role for ARID2, a PBAF (Polybromo - Brg1 Associated Factor)-specific subunit, in meiotic division. Arid2cKO spermatocytes arrest at metaphase-I and are deficient in spindle assembly, kinetochore-associated Polo-like kinase1 (PLK1), and centromeric targeting of Histone H3 threonine3 phosphorylation (H3T3P) and Histone H2A threonine120 phosphorylation (H2AT120P). By determining ARID2 and BRG1 genomic associations, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…In Figure C, most components of the BAF ATPase module, BAF-core, and PBAF-specific were upregulated in the P and D phases, whereas cBAF-specific components presented high expression levels in the L and Z phases. Participation of the PBAF in meiosis rather than cBAF was reported by Menon et al, whose results basically agreed with the abundance changes of PBAF-related components in this study. The Drosha complex, which can initiate miRNA processing, was reported to be an essential factor mediating miRNA production for normal spermatogenesis and male fertility .…”
Section: Resultssupporting
confidence: 93%
“…In Figure C, most components of the BAF ATPase module, BAF-core, and PBAF-specific were upregulated in the P and D phases, whereas cBAF-specific components presented high expression levels in the L and Z phases. Participation of the PBAF in meiosis rather than cBAF was reported by Menon et al, whose results basically agreed with the abundance changes of PBAF-related components in this study. The Drosha complex, which can initiate miRNA processing, was reported to be an essential factor mediating miRNA production for normal spermatogenesis and male fertility .…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, we showed that the SWI/SNF PBAF subcomplex activates genes essential for reductional meiosis and gamete formation (Menon et al, 2021). These data highlight that distinct SWI/SNF subcomplexes govern specific meiotic transitions.…”
Section: Discussionmentioning
confidence: 61%
“…Arid1a WT and Arid1a cKO mice were examined with indirect immunofluorescence (IF). 8-10 μm thick cryosections of testes were prepared using published methods (Menon et al, 2021).…”
Section: Immunofluorescence Staining Of Testis Cryosection and Sperma...mentioning
confidence: 99%
“…The overrepresented pathways enriched in testis-specific genes were related to epigenetic regulation, DNA repair, P53 activity regulation, and chromatin organization, which can be explained by the fact that the genes involving meiosis, DNA repair were required in spermiogenesis to produce a large number of sperms [ 39 ] ( Figure 5f ). For example, a gene ARID2 involved in chromatin organization can regulate chromatin organization in metaphase-I spermatocytes, the deletion of which can result in a metaphase-I arrest because of the dysregulation of cell division core genes [ 40 ].…”
Section: Resultsmentioning
confidence: 99%